The Portuguese University and the crisis of the end of the fourteenth century: Gains and losses - Vilar, Hermínia Vasconcelos (2021)
In Portugal, as in other kingdoms, the last decades of the fourteenth century were marked by a significant economic and political turbulence. To the more general context dominated by the Hundred Years' War and by the Western Schism, Portugal joined the effects of a dynastic and economic crisis increased by the wars with Castile. Against this background, the University, through its teachers and scholars, has developed different strategies, which, almost always, have tried, in one hand, to reinforce or to maintain the relation between University and royal power and, on the other hand, to increase the ever-scarce income that supported the General Study. And, indeed, both kings Fernando and João I were responsible for the donation or recognition of many privileges, but this support was not match by a substantial increase in income, despite the repeated requests of the Study and the economic difficulties manifested. At the same time the effects of the changes of obedience on the part of king Fernando, in the context of the Schism of the West, were also felt at the level of the University. Different petitions addressed to the different Popes as well as various and numerous privileges donated by Rome and Avignon, gave us a glimpse over the inevitable effects of this changes inside the University. The purpose of this paper is, therefore, to analyse and reflect on the role of the University in this period of the late 14th century, assessing the gains and losses that the strategies developed by some of the members of the Study made possible.